Spiritual care in the undergraduate nursing degree in Portugal - Afonso, Ana (2023)
Spiritual care is an essential dimension of holistic care. The purpose of this study was to identify the explicit presence of spiritual care in undergraduate nursing curricula in Portugal. Data were collected through a search in the syllabuses of undergraduate nursing degrees as displayed on the websites of higher education institutions (HEI). Of the 36 HEI, none had a course unit entitled (with title or subtitle) spirituality or spiritual care, even though all the HEI describe a common mission related to preparing nursing students for holistic care.